Дисперсионное уравнение одномерного магнитофотонного кристалла с ферритовым слоем - Шматько, А. А.; Мизерник, В. Н.; Одаренко, Е. Н.; Галенко, А. Ю. (ХНУ імені В.Н. Каразіна, 2016)
In this work we obtain the dispersion relation for magnetophotonic one-dimensional crystal with a gyrotropic ferrite layer in the analytical form. The numerical analysis of the dispersion relation for waves in the crystal at different parameters of the effective permeability of the ferrite layer is carried out. We predict the propagation of bulk fast and slow waves in such structures. The transmission and forbidden bands in the dispersion diagram for the bulk waves are presented in the area of surface ferrite waves.
Keywords: магнитофотонные одномерные кристаллы; гиромагнитные среды; феррит с поперечным магнитным полем; дисперсионная характеристика; полосы пропускания и запирания